Research in law and economics. Vol. 25 - Kirkwood, John B.; Zerbe, Richard O. (Research in law and economics., 2012)
Since 1979 Research in Law and Economics has been presenting original research that explores the extent to which the constraints of law explain economic behavior and the role of economics in forming the law. The first chapter in this volume proposes three different definitions for market power from an antitrust perspective. Chapter two suggests a new means of measuring market power by moving away from traditional indicators of averaging industry profits. The third chapter is an analysis of efforts exerted and utilities obtained in a double lawsuit. Chapter four surveys recent developments in economics of contract interpretation. The fifth chapter examines the impact of changes in foreign exchange legislation on the levels of R&D undertaken by pharmaceutical firms in India. Chapter six addresses the role of transaction costs in explaining governance in environmental economics can play in helping choose environmental policy tools.